2016
DOI: 10.1098/rsta.2016.0054
|View full text |Cite
|
Sign up to set email alerts
|

Lead isotope exchange between dissolved and fluvial particulate matter: a laboratory study from the Johor River estuary

Abstract: One contribution of 20 to a discussion meeting issue 'Biological and climatic impacts of ocean trace element chemistry'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 62 publications
3
25
0
Order By: Relevance
“…The pattern of large enrichments of some metals (V, Cr, Ni, Cu, Zn and Pb) and small enrichments of others (Mn, Fe and also other elements including Ba, U, Th and rare earth elements) is seen in many datasets [12,13,15,38,67] and has persisted for many years, with similar values and patterns evident in data from the 1970s [64]. Lead, for which there has been a significant change owing to elimination of lead additions to automobile fuels [68], is an exception to this. The magnitude of enrichments is reduced in very dusty air masses such those from the Sahara, owing to the anthropogenic component being diluted by the dust component, as is evident from comparing enrichments in air arriving at Cape Verde from the north after passage over the North Atlantic for several days (table 5 and [13]) to the average of all air masses arriving at Cape Verde which therefore include air masses strongly influenced by Saharan dust [12].…”
Section: Atmospheric Deposition Of Other Trace Elementsmentioning
confidence: 99%
“…The pattern of large enrichments of some metals (V, Cr, Ni, Cu, Zn and Pb) and small enrichments of others (Mn, Fe and also other elements including Ba, U, Th and rare earth elements) is seen in many datasets [12,13,15,38,67] and has persisted for many years, with similar values and patterns evident in data from the 1970s [64]. Lead, for which there has been a significant change owing to elimination of lead additions to automobile fuels [68], is an exception to this. The magnitude of enrichments is reduced in very dusty air masses such those from the Sahara, owing to the anthropogenic component being diluted by the dust component, as is evident from comparing enrichments in air arriving at Cape Verde from the north after passage over the North Atlantic for several days (table 5 and [13]) to the average of all air masses arriving at Cape Verde which therefore include air masses strongly influenced by Saharan dust [12].…”
Section: Atmospheric Deposition Of Other Trace Elementsmentioning
confidence: 99%
“…By this, we mean that in the open ocean with relatively low particulate concentrations and minimal sediment interactions we expect Pb to behave in a quasi-conservative manner over short mixing timescales. Although other work has demonstrated that isotopic exchange with particles can influence the dissolved Pb isotope composition (Wu et al, 2010;Chen et al, 2016), this occurs over much longer timescales than the mixing of Norwegian Sea water and LSW to form ISOW. Using our Pb data for Station 32 and the eOMP analysis that the deepest samples are 100 % ISOW and ∼ 20 % LSW (García-Ibáñez et al, 2017), we back-calculate a Norwegian Sea water that is ∼ 7 pmol kg −1 and 206 Pb / 207 Pb ∼ 1.180.…”
Section: Iceland Basin (S32-s36) and Reykjanes Ridge (S38)mentioning
confidence: 99%
“…24 National and international research programs such as GEOTRACES (www.geotraces.org) have been rapidly expanding our knowledge about the temporal and spatial distributions of Pb, and other trace elements, along with the internal cycling and equilibrium exchange of Pb between dissolved, colloidal, and particulate phases. 25,26 Recent studies report the distributions of Pb in the northwest Pacific Ocean, 27 eastern tropical Atlantic Ocean, 24 North Atlantic Ocean, 19 and the North Subarctic Atlantic including the Iceland Basin and the Irminger and Labrador Seas. 23 Nonetheless, the geochemistry of Pb in other regions, such as the Arctic Ocean, is still poorly characterized.…”
Section: ■ Introductionmentioning
confidence: 99%